Analytical and Clinical Evaluation of the Semiquantitative Elecsys Anti–SARS-CoV-2 Spike Protein Receptor Binding Domain Antibody Assay on the Roche cobas e602 Analyzer. Issue 1 (31st August 2021) - Chan, Clarence W; Yi, Xin; Lenza, Michael; Baldwin, Angel D; Jakalski, Jennifer; Tesic, Vera; Yeo, Kiang-Teck J
Abstract: Objectives: To analytically and clinically evaluate the semiquantitative Elecsys anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein antibody (S-Ab) assay on the Roche cobas e602 analyzer. Methods: The S-Ab assay is a 1-step, double-antigen sandwich electrochemiluminescent immunoassay that semiquantitatively measures total IgG, IgM, and IgA antibodies specific for the receptor binding domain of SARS-CoV-2 spike protein in serum or plasma. The S-Ab assay was evaluated for precision, linearity, interference (by hemoglobin, bilirubin, triglycerides, and biotin), cross-reactivity, and clinical performance, and was compared to the qualitative Elecsys anti-nucleocapsid (N-Ab) immunoassay, a lateral flow device that qualitatively detects S-Ab and N-Ab, and an anti-spike enzyme-linked immunosorbent assay (ELISA). Results: S-Ab assay is precise, exhibits linearity from 0.4 to 250 U/mL, is unaffected by significant cross-reactivity or interferences, and qualitatively demonstrates greater than 90% concordance with N-Ab assay and lateral flow device. Readouts of S-Ab assay correlate with ELISA, which in turn correlates strongly with SARS-CoV-2 virus neutralization assay, and exhibit 100% sensitivity and specificity for COVID-19 patient samples obtained at or more than 14 days after PCR positivity. Conclusions: The S-Ab assay is a robust clinical test for qualitative and semiquantitative detection of seropositivity following SARS-CoV-2 infection or spike-encoding mRNA COVID-19 vaccination.